Municipal Solid Waste Composition Study of Selected Area in Gambang, Pahang - Wan Faizal, Wan Ishak; Nadiah, Mokhtar; Noor Suraya, Romali; Siti Fatimah, Che Osmi; Mohd Armi, Abu Samah (IOP Science, 2013)
The amount of municipal solid waste (MSW) generated continue to increase in response to rapid growth in population, change in life style and accelerated urbanization and industrialization process. The study on MSW is important in order to determine the composition further seeks an immediate remedy to minimize the waste generated at the early stage. As most of the MSW goes to the landfill or dumping sites, particularly in Malaysia, closure of filled-up landfill may become an alarm clock for an immediate action of proper solid waste management. This research aims to determine the waste composition generated from selected residential area at Gambang, Kuantan, Pahang which represent Old residential area (ORA), Intermediate residential area (IRA) and New residential area (NRA). The study was conducted by segregating and weighing solid waste in the residential area into 6 main components ie., food waste, paper, plastic, glass, metal and others. In a period of four weeks, samples from the residential unit were taken and analyzed. The MSW generation rates were recorded vary from 0.217 to 0.388 kg person−1day−1. Food waste has become the major solid waste component generated daily which mounted up to 50%. From this research, the result revealed that the recyclable composition of waste generated by residents have a potential to be reuse, recycle and reduce at the point sources.